Stigma of People Living with HIV/AIDS - I Gede Juanamasta; Nursalam Nursalam; Ferry Efendi; Rio Ady Erwansyah (NurseLine Journal, 2019)
People living with HIV have many complex problems in their lives. Internal problems concern bio-psycho-socio-spiritual, while external problems concern the views and attitudes of others towards themselves. Negative views from other people formed long ago will give a bad stigma to people with HIV. The stigma of society has a great influence, not only affecting citizens but also health workers. This study aims to review the results of research related to stigma inherent in the community, especially nurses to people with HIV. The researcher sought the results of other studies through several databases including ProQuest, Scopus, Science Direct, PubMed, Medline, Springer link and Elsevier. Keywords to search literature include "stigma", "nurse" and "people with HIV". The results obtained were as many as 14 journals. Many studies have been carried out for prevention, treatment, and support for people with HIV / AIDS. But along with advances in the field of health need to continue to do problems related to people with HIV / AIDS.